Damage cause and mechanism of well-vegetated soil slopes under extreme rainfall: a case study - Chen, Jingye; Gong, Qinghua; Wang, Jun; Yuan, Shaoxiong (Frontiers in Earth Science, 2024)
A substantial number of shallow landslides can still occur in areas with high vegetation cover under extreme rainfall. The cause and mechanism of this type of landslide remain unknown, and thus a case study is selected for study in this paper. The extreme rainfall from June 10-13, 2019, caused mass landslides throughout Mibei Village. Most landslides happened in well-vegetated areas, and some even transformed into debris flows. This paper presents detailed field investigations on 31 of them, the result of which were used to perform numerical simulations and ring shear tests. The objective of this study was to investigate the damage cause and mechanism of well-vegetated soil slopes under extreme rainfall. The results indicate that vegetation exerts a dual effect on slope stability. Within the rhizosphere zone, roots significantly enhance the soil shear strength, thereby reducing the likelihood of slope instability. Simultaneously, the rhizosphere zone exhibits enhanced permeability and acts as a relatively impermeable layer at the bottom, which makes the shallow layer of the slopes more easily saturated by rainfall infiltration. The slopes are prone to instability at the soil layer situated below the bottom of the rhizosphere zone, and mostly are translational slides with suddenness. The main triggering factor for the landslide is the presence of positive pore water pressure in the soil, which makes the matrix suction lost and the effective stress reduced. The slip zone soil exhibits negative dilatancy, while the saturated slip soil undergoes liquefaction, which can make landslides conversion into debris flows.